2014
DOI: 10.1371/journal.pone.0105342
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Simultaneously Induced G0/G1-Phase Arrest and MAPK-Mediated Mitochondrial-Derived Apoptosis in Human Acute Myeloid Leukemia Cell Lines

Abstract: BackgroundPterostilbene (PTER) is a dimethylated analog of the phenolic phytoalexin, resveratrol, with higher anticancer activity in various tumors. Herein, the molecular mechanisms by which PTER exerts its anticancer effects against acute myeloid leukemia (AML) cells were investigated.Methodology and Principal FindingsResults showed that PTER suppressed cell proliferation in various AML cell lines. PTER-induced G0/G1-phase arrest occurred when expressions of cyclin D3 and cyclin-dependent kinase (CDK)2/6 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…First, we demonstrated that pterostilbene showed a dose-dependent cytotoxic effect on six human DLBCL cell lines, OCI-LY8, SUDHL-4, DB, TMD8, U2932, and NU-DUL-1 (Fig. 1A) with an approximate IC 50 of 30 μM after 48 h. Pterostilbene-induced cell proliferation, in a concentration-dependent fashion, has also been observed in other hematological malignancies, including acute myeloid leukemia (AML)14 and MOLT4 human lymphoblastic leukemia32. In addition, we also found that pterostilbene-induced cell viability was not inhibited in a time-dependent manner in three DLBCL cell lines (SUDHL-4, DB and NU-DUL-1) within the setting concentration range.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…First, we demonstrated that pterostilbene showed a dose-dependent cytotoxic effect on six human DLBCL cell lines, OCI-LY8, SUDHL-4, DB, TMD8, U2932, and NU-DUL-1 (Fig. 1A) with an approximate IC 50 of 30 μM after 48 h. Pterostilbene-induced cell proliferation, in a concentration-dependent fashion, has also been observed in other hematological malignancies, including acute myeloid leukemia (AML)14 and MOLT4 human lymphoblastic leukemia32. In addition, we also found that pterostilbene-induced cell viability was not inhibited in a time-dependent manner in three DLBCL cell lines (SUDHL-4, DB and NU-DUL-1) within the setting concentration range.…”
Section: Discussionmentioning
confidence: 78%
“…4A, the result indicates that pterostilbene was capable of disrupting the MMP and, thus, of activating the intrinsic apoptosis pathway. Moreover, previous studies have reported that oxidative stress induced by pterostilbene originates from increasing levels of reactive oxygen species (ROS) in HL-60 cells14 and breast cancer cells13, and ROS are principal mediators of the ROS-dependent MMP apoptosis pathway. To investigate whether pterostilbene induces intracellular oxidation, we evaluated ROS levels in treated four DLBCL cell lines by flow cytometry using the specific oxidation-sensitive fluorescent dyes DCFH-DA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the MAPK signaling pathway (especially c-jun N-terminal kinase (jNK) and p38 MAPK) is essential for Pter-mediated activation of caspases (21). Another study has reported that a potent pan-PI3K/Akt inhibitor enhances the apoptotic effects of bortezomib in bortezomibresistant cells significantly, suggesting the roles of these signaling pathways in Pter-induced apoptosis (22).…”
Section: Pter Induces Apoptosis Of H929r Cells In a Dose-and Time-depmentioning
confidence: 99%
“…Pterostilbene [(E)-3,5-dimethyl-4-hydroxyl phenyl ethylene] is a 3,5-dimethyl derivative of resveratrol. It is one among the non-flavonoid polyphenol compounds that are found in grapes, nuts, strawberry, Guangxi dragon's blood, and propolia (Hsiao et al, 2014;Sato et al, 2014). Pterostilbene has activities that are similar to those of resveratrol, and shows multiple activities including antifungal, antiproliferative, antioxidant, anti-inflammatory, and antilipidemic activities.…”
Section: Introductionmentioning
confidence: 99%